ROWING SPORT IN LEARNING FRACTIONS OF THE FOURTH GRADE STUDENTS - Marhamah Fajriyah Nasution; Ratu Ilma Indra Putri; Zulkardi Zulkardi (Journal on Mathematics Education, 2018)
This study aimed to produce learning trajectory with rowing context that can help students understand addition and subtraction of fractions. Subject of the research were students IV MIN 2 Palembang. The method used was research design with three stages, those are preparing for the experiment, the design experiments, and the retrospective analysis. Learning trajectory was designed from in-formal stage to the formal stage. At the informal stage, Rowing was used as a starting point to explore the students’ knowledge of fractions. Data collection conducted through video recordings and photos to see the learning process in the classroom, written tests, observation and interviews during the learning process with the students which is the subject of research. Research produced learning trajectory consisting of a series of learning addition and subtraction of fractions dealing with the rowing. The results showed that the use of the rowing can be a bridge of students' thinking and help students in understanding the operation of addition and subtraction of fractions.DOI: http://dx.doi.org/10.22342/jme.9.1.4270.69-80